Influence of Mold Material on the Mold Stability for Foundry Use - Sinha N.K.; Choudhary I.N.; Singh J.K. (My University, 2025)
In CO2 molding process, sodium silicate is used as a binder to form a chemical bond to have high strength, good dimensional accuracy, etc. as compared to green sand mold. The mold materials are for present investigation wis. silica sand (ss), red mud (rdm), blast furnace slag (bfs), ferrochrome slag (fcs) and olivine sand (olv). This paper investigates the mold properties such as shear strength, compressive strength, hardness, and permeability as per to the American Foundrymen Society (AFS) standard. The mold properties of these mold materials were investigated for the stability as a mold, as compared with silica sand mold for foundry use. And also investigated the effect of mold material on the morphology of phases of the microstructure of Al-Si alloy cast in a different mold. The result shows that the mold properties of blast furnace slag were better as compared to silica sand mold; the mold properties such as shear strength, compressive strength, hardness and permeability of blast furnace slag mold and silica sand mold are 7.2 psi, 17.5 psi, 88, 630; 6.9 psi, 15.4 psi, 92, 480 respectively. The A319 alloy cast in slag mold having less porosity, lower value of secondary dendritic arm spacing (SDAS), and high tensile strength as compared to silica sand mold. Graphical Abstract: [Figure not available: see fulltext.] © 2021, Springer Nature B.V.